2020
DOI: 10.1108/edi-02-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant perceptions of integration in the Canadian workplace

Abstract: PurposeThis paper explores integration experiences of immigrants in the Canadian workplace from the perspective of immigrants themselves, focusing on cultural capital and cultural judgments as factors influencing workplace entry, advancement and social integration in an increasingly diverse work environment.Design/methodology/approachAn interpretive approach that involved thematic analysis of in-depth interview data was employed.FindingsThe findings reveal that the official two-way multiculturalism policy of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…He stated, "Regardless of whether you're educated here or not-racialized folks do not get hired at the same rate". These respondents confirmed what research has shown, that racialized newcomers experience exclusion entering the job market based on stereotypes of language fluency and skill aptitude based on perceptions of racialized names and educational context (Oreopoulos 2011;Block and Galabuzi 2018;Ertorer et al 2020). A lack of Canadian experience was also noted as a barrier for employment, yet, as highlighted by a director at a local research centre (Sarah), "they don't put this requirement [Canadian experience] in job ads anymore, but they do ask about it in the interview itself".…”
Section: Barriers Facing Racialized Immigrants or Racialized Canadianssupporting
confidence: 77%
“…He stated, "Regardless of whether you're educated here or not-racialized folks do not get hired at the same rate". These respondents confirmed what research has shown, that racialized newcomers experience exclusion entering the job market based on stereotypes of language fluency and skill aptitude based on perceptions of racialized names and educational context (Oreopoulos 2011;Block and Galabuzi 2018;Ertorer et al 2020). A lack of Canadian experience was also noted as a barrier for employment, yet, as highlighted by a director at a local research centre (Sarah), "they don't put this requirement [Canadian experience] in job ads anymore, but they do ask about it in the interview itself".…”
Section: Barriers Facing Racialized Immigrants or Racialized Canadianssupporting
confidence: 77%
“…The employment of migrant workers in receiving countries has become an important area of research for employment relations and management scholars (McGovern, 2007; Rodriguez and Mearns, 2012; Wright and Clibborn, 2019). Research suggests that migrant workers are more likely to face unfavorable treatment at work (Akinlade et al , 2020; Esses, 2021) and experience greater difficulty integrating into the workforce (Ertorer et al , 2020; Hamrin, 2019). Furthermore, migrant workers are increasingly channeled into precarious employment “characterized by uncertainty, low income, and limited social benefits and statutory entitlements” (Vosko, 2010, p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…, 2018). By developing a friendly work environment for culturally diverse employees, SIEs who wish to leave the organization may need to consider the sacrifices they have to make (Ertorer et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Organizations may create opportunities for SIEs to work and collaborate in teams to strengthen the organizational links (Soltis et al, 2018). By developing a friendly work environment for culturally diverse employees, SIEs who wish to leave the organization may need to consider the sacrifices they have to make (Ertorer et al, 2020). Organizations can increase SIEs' community embeddedness by supporting community programs (i.e.…”
Section: Practical Implicationsmentioning
confidence: 99%